1997
DOI: 10.1016/s0009-9236(97)90138-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of antiglaucoma drugs on ocular hemodynamics in healthy volunteers

Abstract: Our results indicate that befunolol, metipranolol, timolol, clonidine, and dipivefrin reduce choroidal and optic disc blood flow. This could be caused by drug diffusion to the choroid, which may cause vasoconstriction. Ocular blood flow reduction was not observed with betaxolol, levobunolol, or pilocarpine. The lack of effect of all drugs under study on central retinal blood flow velocity might partially be the result of autoregulative mechanisms. Because optic nerve head blood flow likely plays a critical rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
2
3

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 40 publications
4
55
2
3
Order By: Relevance
“…16 In another study assessing fundus pulsations, topical clonidine or dipivefrin significantly decreased fundus pulsations in the macula and the optic disc. 45 In the present study in rabbits, the ipsilateral significant decrease of both NB ONH by maximum of 9% and NB CH by maximum of 20% in the phenylephrinetreated eyes was evident at 30 min after the instillation and continued over an hour, whereas no significant change was found in the contralateral eyes. The IOP showed a tendency to decrease in the phenylephrinetreated eyes, as previously studied in rabbits, 46 whereas the blood pressure remained unchanged.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…16 In another study assessing fundus pulsations, topical clonidine or dipivefrin significantly decreased fundus pulsations in the macula and the optic disc. 45 In the present study in rabbits, the ipsilateral significant decrease of both NB ONH by maximum of 9% and NB CH by maximum of 20% in the phenylephrinetreated eyes was evident at 30 min after the instillation and continued over an hour, whereas no significant change was found in the contralateral eyes. The IOP showed a tendency to decrease in the phenylephrinetreated eyes, as previously studied in rabbits, 46 whereas the blood pressure remained unchanged.…”
Section: Discussioncontrasting
confidence: 42%
“…45 On the other hand, it is not clear whether the increased RI in the temporal retinal artery is attributed to direct effect of phenylephrine on the retinal branch arteries or central retinal artery. No significant change in the blood flow despite the increased RI may be explained by autoregulatory mechanism of retinal circulation.…”
Section: Discussionmentioning
confidence: 99%
“…79 In contrast, studies conducted in patients with glaucoma as well as in healthy volunteers found no effect of pilocarpine on the pulsatile component of ocular blood flow. 80,81 There is no study supporting that parasympathomimetics exert any non-IOPrelated neuroprotective effects in glaucoma patients.…”
Section: Topical Therapiesmentioning
confidence: 99%
“…The short-term and day-to-day variability of the method is small, which allows detection of even minor changes in local pulsatile blood flow following pharmacological stimulation. 11 In contrast to systems recording ocular pressure pulse, 12-14 information on the ocular circulation can be obtained with high transverse resolution. To obtain information on the choroidal blood flow, the macula, which lacks retinal vasculature, was chosen for measurements.…”
Section: Fundus Pulsationsmentioning
confidence: 99%